2020
DOI: 10.1155/2020/9353975
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Comparisons of Different Combinations of Yigan Jiangzhi Formula in Rats: Simultaneous Determination of Fourteen Components by UPLC-MS/MS

Abstract: A rapid, specific, and sensitive analysis for simultaneous determination of fourteen components (daidzein, fermononetin, apigenin, luteolin, puerarin, ononin, calycosin-7-O-β-D-glucoside, tanshinol, rosmarinic acid, alkanoic acid, salvianolic acid B, berberine, jatrorrhizin, and palmatine) of Yigan Jiangzhi formula (YGJZF, a clinical experienced formula for damp-heat syndrome) in rat plasma was developed and validated using ultraperformance liquid chromatography coupled with mass spectrometry. Lower limit of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…After oral administration of Chrysanthemum morifolium extract to rats at 1.7 g/kg body weight, equivalent to 22.8 and 58.3 μmol/kg of luteolin and luteolin-7-O-glucoside, respectively, luteolin and its glycosides were quickly absorbed and luteolin, luteolin monoglucoside, and luteolin monoglucuronide were easily detected in the plasma with the highest levels of pure luteolin observed 1 h after oral administration, corresponding to 0.76 ± 0.27 μM ( 68 ). Although this result appears to be quite far from the dosage used here, the absorption rate of luteolin is known to be dose- and time- dependent with plasma concentrations, increasing several-fold after repeated administration or higher doses, especially if it is coadministered with other ingredients ( 69 ). Moreover, the levels of absorbed luteolin, detected in plasma in the free form, can reach the values used in our work (25 μM) by formulation with lipid carriers ( 70 ).…”
Section: Discussionmentioning
confidence: 78%
“…After oral administration of Chrysanthemum morifolium extract to rats at 1.7 g/kg body weight, equivalent to 22.8 and 58.3 μmol/kg of luteolin and luteolin-7-O-glucoside, respectively, luteolin and its glycosides were quickly absorbed and luteolin, luteolin monoglucoside, and luteolin monoglucuronide were easily detected in the plasma with the highest levels of pure luteolin observed 1 h after oral administration, corresponding to 0.76 ± 0.27 μM ( 68 ). Although this result appears to be quite far from the dosage used here, the absorption rate of luteolin is known to be dose- and time- dependent with plasma concentrations, increasing several-fold after repeated administration or higher doses, especially if it is coadministered with other ingredients ( 69 ). Moreover, the levels of absorbed luteolin, detected in plasma in the free form, can reach the values used in our work (25 μM) by formulation with lipid carriers ( 70 ).…”
Section: Discussionmentioning
confidence: 78%
“…The Acquity UPLC BEH C 18 column was selected as it had a great separation efficiency (Zhang et al, 2018). A previous study has investigated different mobile phase compositions, and found that acetonitrile–water was good at lowing background noise and contained great elutive power (Wang et al, 2020). In addition, researchers have also demonstrated that adding 0.1% formic acid to the mobile phase can provide better peak shape and separation degree (Shen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because of hydroxyl groups found within the chemical structure of calycosin, they are metabolized to glucuronide by phase II metabolic enzymes such as UDP-glucuronosyltransferases from the intestine and liver after oral administration [ 65 ]. In addition to the role of metabolism, absorption, hydrolysis, efflux, and intestinal circulation in the intestinal tract also participate in the disposal of calycosin in the body, affecting their systemic and local bioavailability [ 66 ].…”
Section: Pharmacokinetics Of Calycosinmentioning
confidence: 99%